2018
DOI: 10.1002/celc.201800047
|View full text |Cite
|
Sign up to set email alerts
|

Conserved Histidine Adjacent to the Proximal Cluster Tunes the Anaerobic Reductive Activation of Escherichia coli Membrane‐Bound [NiFe] Hydrogenase‐1

Abstract: Abstract[NiFe] hydrogenases are electrocatalysts that oxidize H2 at a rapid rate without the need for precious metals. All membrane‐bound [NiFe] hydrogenases (MBH) possess a histidine residue that points to the electron‐transfer iron sulfur cluster closest (“proximal”) to the [NiFe] H2‐binding active site. Replacement of this amino acid with alanine induces O2 sensitivity, and this has been attributed to the role of the histidine in enabling the reversible O2‐induced over‐oxidation of the [Fe4S3Cys2] proximal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Specific residues in the vicinity of the active site have been named as responsible for the proton transfer while the Fe–S cluster closest to the active site is regarded as the source of the electron. Both experimental and theoretical studies confirmed the central role an unusual [4Fe‐3S] proximal cluster featuring extra two Cys played with respect to O 2 tolerance of several [NiFe] hydrogenases (Flanagan, Chidwick, Walton, Moir, & Parkin, ; Fritsch, Scheerer, et al, ; Pandelia et al, ; Roessler, Evans, Davies, Harmer, & Armstrong, ; Shomura, Yoon, Nishihara, & Higuchi, ; Volbeda et al, ). These extra Cys in the vicinity of the Fe–S cluster enable rapid electron transfer to the active site and contribute to O 2 tolerance; however, the molecular mechanism(s) enabling transfer acceleration is(are) yet to be discovered.…”
Section: O2 Inactivation and Protection Mechanismmentioning
confidence: 77%
“…Specific residues in the vicinity of the active site have been named as responsible for the proton transfer while the Fe–S cluster closest to the active site is regarded as the source of the electron. Both experimental and theoretical studies confirmed the central role an unusual [4Fe‐3S] proximal cluster featuring extra two Cys played with respect to O 2 tolerance of several [NiFe] hydrogenases (Flanagan, Chidwick, Walton, Moir, & Parkin, ; Fritsch, Scheerer, et al, ; Pandelia et al, ; Roessler, Evans, Davies, Harmer, & Armstrong, ; Shomura, Yoon, Nishihara, & Higuchi, ; Volbeda et al, ). These extra Cys in the vicinity of the Fe–S cluster enable rapid electron transfer to the active site and contribute to O 2 tolerance; however, the molecular mechanism(s) enabling transfer acceleration is(are) yet to be discovered.…”
Section: O2 Inactivation and Protection Mechanismmentioning
confidence: 77%
“…4). This cluster-proximal histidine is commonly found in NiFe hydrogenases (34) and thermostable ferredoxins (15,35). Titration of this histidine results in a significant shift in midpoint potential for these naturally occurring ferredoxins (36).…”
Section: Resultsmentioning
confidence: 99%
“…FNR AF has an Asp to His substitution at position 22. Interestingly, it has been found that juxtaposition of His to the cysteine-coordinated [4Fe-3S] 2+ center of a subgroup of Ni hydrogenases provides stability in the presence of O 2 (Frielingsdorf et al, 2014; Flanagan et al, 2018). Also, substitution of Leu 28 by the positively charged His has been shown to stabilize the [4Fe-4S] 2+ center in FNR EC in the presence of O 2 (Bates et al, 2000) perhaps by hindering conformational flexibility of the region (Volbeda et al, 2015).…”
Section: Resultsmentioning
confidence: 99%